The mirage of international criminal law : Kant's metaphysics of mens rea - Malekian, Farhad (Cambridge Scholars Publishing, 2018)
"This book explores, from various perspectives, Kants codex of the categorical imperative and the supreme principle of morality in juxtaposition with the monopolisation of the rules of international criminal law. Kants reference to the term propensity to evil in human nature is a much more serious iniquity universally in the nature of the Security Council than the concepts of a mens rea and actus reus in criminal law. His decisive warning foreshadows that the inclinations towards self-interest, self-love, and intent in collective mens rea within the resolutions of the Security Council prevent states from striving towards the supreme maxim of a genuine international moral worth. The idea of international criminal law is, thus, viewed as a mirage. Essentially, certain rules of the United Nations Charter, the system of international criminal justice, human rights law, and humanitarian law, like a fata morgana, are crucial if unattainable. The permanent members of the Security Council are deceiving the world by propagating a variety of excuses with the core objective of economic gain"--Back cover